2022
DOI: 10.1177/15266028221108659
|View full text |Cite
|
Sign up to set email alerts
|

Suprarenal Aortic Occlusion Due to Coral Reef Calcification: Successful Endovascular Management Assisted by Intravascular Lithotripsy and Visceral Protection

Abstract: Purpose: Suprarenal aortic occlusion due to coral reef calcification has been considered not suitable for endovascular therapy because of visceral artery involvement. Unfortunately, open surgical treatment also carries high morbidity and mortality. We describe here successful endovascular management of a case of suprarenal aortic occlusion due to coral reef calcification with the use of intravascular lithotripsy (IVL) and visceral protection. Case Report: A 72-year-old women presented with uncontrolled hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…While recent advances in endovascular techniques, including stent grafts and lithotripsy, have shown promise in managing aortic stenosis in CRA, their use is limited to specific cases because of potential occlusion of the vital aortic branches, particularly in cases with visceral involvement. Additionally, lithotripsy carries the risk of embolization and requires the use of protection devices [ 17 , 18 ]. The systematic review by Baldaia et al [ 2 ], which involved 124 CRA cases, revealed that 88.7% of patients underwent open surgery, 8.9% received endovascular treatment, and 2.4% had laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While recent advances in endovascular techniques, including stent grafts and lithotripsy, have shown promise in managing aortic stenosis in CRA, their use is limited to specific cases because of potential occlusion of the vital aortic branches, particularly in cases with visceral involvement. Additionally, lithotripsy carries the risk of embolization and requires the use of protection devices [ 17 , 18 ]. The systematic review by Baldaia et al [ 2 ], which involved 124 CRA cases, revealed that 88.7% of patients underwent open surgery, 8.9% received endovascular treatment, and 2.4% had laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the last decade, the endovascular method seems to make its appearance and is the protagonist in the treatment of selected patients with CRA who cannot be treated with the open method. According to the current literature and platforms, the terms “endovascular stent-graft therapy” and “coral reef aorta” coexist and appear since 2008, and since then, only 13 articles ( Table 1 ) 3 4 5 8 10 11 12 13 14 15 16 17 18 have been published, most of them in the past 3 years. This is probably because vascular surgeons' familiarity with the endovascular technique and the appearance of newer and more advanced endovascular tools encourage vascular surgeons to dare to use the method.…”
Section: Discussionmentioning
confidence: 99%
“…Recorded cases of endovascular treatment with stent graft of coral reef aorta reported in bibliographic databases and platforms[3][4][5]8,[10][11][12][13][14][15][16][17][18] …”
mentioning
confidence: 99%